2014
DOI: 10.1007/s13277-014-2517-5
|View full text |Cite
|
Sign up to set email alerts
|

miR149 rs71428439 polymorphism and risk of clear cell renal cell carcinoma: a case–control study

Abstract: Clear cell renal cell carcinoma (CCRCC) is the most common subtype of renal cell cancer and accounts for 70 % of renal cell cancer. CCRCC remains an enigmatic tumor type, as the molecular genetic mechanisms are still unclear. MicroRNA (miR) 149 functions as a tumor suppressor and plays an important role in the carcinogenesis of renal cells. In this study, we enrolled 1,000 CCRCC patients and 1,000 cancer-free controls to evaluate the association of miR149 rs71428439 with the risk of CCRCC by a case-control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…[79, 80] The study from Wang Z et al also demonstrated that the GG genotypes of miR-149-5p rs71428439 increased the risk of clear cell renal cell carcinoma. 81 But miR-149-5p rs2292832 T/C polymorphism could decrease digestive cancer susceptibility in Li L et al's meta-analysis study. 82 Wang et al found that pre-mir-149-5p rs2292382 had significantly better survival in laryngeal squamous cell carcinoma.…”
Section: Mir-149 As Potential Biomarkersmentioning
confidence: 96%
“…[79, 80] The study from Wang Z et al also demonstrated that the GG genotypes of miR-149-5p rs71428439 increased the risk of clear cell renal cell carcinoma. 81 But miR-149-5p rs2292832 T/C polymorphism could decrease digestive cancer susceptibility in Li L et al's meta-analysis study. 82 Wang et al found that pre-mir-149-5p rs2292382 had significantly better survival in laryngeal squamous cell carcinoma.…”
Section: Mir-149 As Potential Biomarkersmentioning
confidence: 96%
“…These made it possible to do a rapid screening of lung cancer risk and drug resistance about A, polymorphisms and risk of lung cancer; B, polymorphisms and evaluation of platinum-based chemotherapy response. MiRNAs are a class of small non-coding RNA molecules, play important roles in many biological and physiological processes, aberrant microRNA expression has been found in several diseases including lung cancer (23)(24)(25)(26)(27)(28). MiR-149 is down regulated in several cancer types (29,30) and is believed to act as a versatile tumor-suppression miRNA by regulating the expression of many genes such as AKT1 (31), GIT1 (32), ZBTB2 (33), FOXM1 (34).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-149 is down regulated in several cancer types (29,30) and is believed to act as a versatile tumor-suppression miRNA by regulating the expression of many genes such as AKT1 (31), GIT1 (32), ZBTB2 (33), FOXM1 (34). Recently studies showed that miR-149 rs71428439 polymorphism was significantly associated with increased clear cell renal cell carcinoma (CCRCC) and hepatocellular carcinoma (HCC) risk (28,35). We didn't find the association of this polymorphism with lung cancer risk in this study, but in NSCLC, female, age under 57 years subgroups, carriers with A allele of this mutation has a higher risk of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and medical treatment seems important in decreasing mortality and increasing total quality of life. Several studies have suggested that genetic factors are involved in the development of RCC (Wang et al, 2014;Meng et al, 2014Meng et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%